Jan Jozua van Nouhuys (1903-1940) : 'n lewensbeskrywing en kritiese waardering van sy werk - Nilant, F.G.E. (Felix Gottlieb Ernst) (University of Pretoria, 2016)
Dissertation (MA)--University of Pretoria, 1971.